Origin analysis of paleo-overpressure in source rocks based on logging response characteristics: a case study of the Chang 7 member in the Triassic Yanchang formation, Longdong area, Ordos Basin, China - Xu, Kaitong; Huang, Yujia; Tang, Minggang; Wu, Jiahao; Ma, Tengfei (Frontiers in Earth Science, 2024)
The identification of the origins of source rock palaeo-overpressure based on logging response parameters is frequently influenced by the presence of organic matter.To accurately identify the paleo-overpressure origin of source rocks and employ an appropriate method for paleo-pressure calculation, this study proposes a quantitative approach to assess the influence of organic matter content on overpressure analysis. The findings demonstrate that the presence of organic matter in Chang 7 shale leads to an increase in acoustic time difference and a decrease in density. After incorporating the multi-component rock equivalent volume model correction, it is evident that the paleo-overpressure observed in the Chang 7 member is not attributed to undercompaction but rather to fluid expansion mechanisms. In conjunction with the acoustic velocity-density palte method, the paleo-overpressure of the Chang 7 member is attributed to undercompaction and expansion resulting from hydrocarbon generation. The pressure evolution of the Chang 7 member has been reconstructed based on the identification of its paleo-overpressure origin. The distribution characteristics of paleo-pressure recovered based on hydrocarbon generation expansion exhibit a strong correlation with the reservoir. The reliability of the correction method for organic matter influence is demonstrated. The proposed method is not only applicable for the investigation of paleo-pressure, but also holds significant implications for the assessment of pressure within organic-rich intervals.